Upaya Meningkatkan Motivasi dan Prestasi Belajar Siswa Pada Materi Alat Optik dengan Menggunakan Media Grafis - Tri Erlina Wati; Effendi Effendi; Siti Anisatur Rofiqah (Pendidikan Fisika Universitas Nurul Huda, 2021)
The purpose of this study was to increase the motivation and learning achievement of eighth-graders at MTs Subulussalam Sriwangi on the concept of optical instruments with the help of graphic media. The type of research used is Classroom Action Research with a qualitative approach. The data in this study were obtained from the results of observations and the results of the final test in each cycle. Based on the results of the study showed that the motivation and learning achievement of students with the help of the use of graphic media has increased. The increase can be seen from the cycle 1 test scores which increased by 72.5% compared to the pre-study test scores, and the second cycle test scores which increased by 82.5% compared to the first cycle test scores. Overall, students' learning motivation increased by 10%. The increase in achievement can be seen from the cycle 1 test scores which increased by 73.80% compared to the pre-research test scores and the second cycle test scores increased by 80.94% compared to the first cycle test scores. Overall, students' learning achievement increased by 7.14%